Development of bacterial blight resistant Mestizo hybrid maintainer and restorer lines through marker-aided backcrossing - Borines, Lucia M.; Espejo, Emilie O.; Piamonte, Robelyn T.; Vera Cruz, Casiana M.; Redoña, Edilberto (Annals of Tropical Research, 2008)
This study was conducted to: 1) evaluate the reaction of Mestizo hybrids, their maintainer and restorer lines to Philippine Xanthomonas oryzae pv. Oryzae races, 2) incorporate bacterial blight resistance genes to these lines via marker-aided backcrossing and 3) confirm the presence of introgressed Xa genes in the progeny of each backcross generation through phenotyping and molecular market analysis. Mestizo hybrids, their maintainer and restorer lines, IRBB62 donor, and checks were inoculated with ten Xoo races (12 isolates). Marker-aided backcrossing from IRBB62 donor (with Xa4/7/21) to each line was done to introgress target genes. The resistance genes in the advanced lines were confirmed using diagnostic Xoo races and analyses of linked DNA markers. Mestizo 1, 2 and 3, their maintainer and restorer lines (IR68888B, IR68897B, IR34686R, IR62161R) except IR58025B were similar to IRBB4 indicating the presence of Xa4 resistance gene in these lines. All the lines however, did not contain the Xa7 and Xa21 genes. Resistance genes Xa7 and Xa21 were incorporated in addition to Xa4 to BC5F2 progeny (BC5F3 seeds) of IR34686-179-1-2-1R, IR60819-34-2R, IR62161-184-3-1-3-2R and IR6888B. Resistance genes were also incorporated to BC4F1 progeny (BC4F2 seeds) of IR58025B and IR68897B. The presence of the genes was confirmed through linked markers. The lines containing gene pyramids had increased resistance to bacterial blight and a wider resistance spectrum to Xoo races. Advanced backcross progeny were phenotypically similar to their recurrent B and R lines.